Introducing teledermoscopy of possible skin cancers in general practice in Southern Denmark. (29th April 2020) - Vestergaard, Tine; Prasad, Sumangali C; Schuster, Annette; Laurinaviciene, Rasa; Bygum, Anette; Munck, Anders; Andersen, Merethe K
Abstract: Background: The increasing incidence of skin cancers poses a burden to health care systems. General practitioners (GPs) play an important role in triaging these diseases and referring relevant patients to specialists. It is challenging to distinguish benign from malignant skin lesions, and GPs may benefit from diagnostic support from teledermoscopy (TD). Objectives: To assess whether the introduction of TD in general practice was feasible and might reduce the number of unnecessary referrals to specialists and to assess the diagnostic accuracy and confidence of participating GPs. Methods: Fifty general practices in Southern Denmark participated. Adult patients presenting to their GP with suspected skin cancer could be included. Images including dermoscopy were taken by the GP and sent for evaluation by specialized dermatologists at a university hospital. Patients were simultaneously referred for a face-to-face evaluation at the university hospital. Diagnoses proposed by the GPs and by TD were compared to the final diagnoses obtained by histopathology or, if not available, face-to-face evaluation. Results: Five hundred and nineteen patients with 600 suspected skin cancers were included. The final diagnosis was benign in 72.3%. The photo quality was good or fair in 90.5%. GPs reported uncertainty about their diagnoses in 41.5% of cases. The GPs' positive predictive values for any malignancy and for malignant melanoma were 49.5% and 26.3%, respectively. On evaluation by TD, 31.5% of lesions did not need further in-person assessment. Conclusion: Useful images of suspicious skin lesions were obtained from general practice, and GPs could benefit from TD to improve their diagnostic accuracy and confidence.